Geographical discrimination of garlic (Allium Sativum L.) based on Stable isotope ratio analysis coupled with statistical methods: The Italian case study. (December 2019) - Pianezze, Silvia; Perini, Matteo; Bontempo, Luana; Ziller, Luca; D'Archivio, Angelo Antonio
Abstract: Stable isotope ratio analysis of the major bioelements (δ 2 H, δ 13 C, δ 15 N, δ 18 O, δ 34 S), considered for the first time as a whole, was used to attempt a geographical characterization of red garlic ( Allium sativum L. ) cultivated throughout different Italian territories (Abruzzo, Lazio and Sicily). Up to now, no official methods are available to determine the geographical origin of this type of product. In this context, the Isotope Ratio Mass Spectrometry method (IRMS) represents a powerful analytical technique. The characteristic ranges of variability of the five isotope ratios in 56 red Italian garlic samples are here presented as well as their relationships. The geographical origin has some influence over the different ratios, although their data distribution shows some overlap when Principal Component Analysis (PCA) is applied. In spite of the relative closeness of the sampling sites, a model with very good predictive performance of the geographical classification was achieved byLinear Discriminant Analysis (LDA) and k-nearest neighbours (k-NN) method. Moreover, preliminary class modelling based on Soft Independent Modelling of Class Analogy (SIMCA) supports the ability of stable isotope ratios analysis for the geographical traceability of garlic. Graphical abstract: Image 1 Highlights: IRMS represents a powerful tool to carry out the analysis on garlic samples. Garlic from close areas can be differentiated according to δ 18 O and δ 2 H. A good geographical classification was achieved by using LDA, k-NN method and SIMCA.